P761 Negative Body Image in Inflammatory Bowel Disease persists despite Modern IBD care. (30th January 2023) - Madigan, S; Prichard, I; Smart, C; Prosser, R; Mountifield, R
Abstract: Background: Body image dissatisfaction (BID) is prevalent in patients with Inflammatory Bowel Disease (IBD). Historically female sex, previous IBD surgery, impaired QoL have been associated with negative body image. The introduction of biologic therapies and modern IBD care in Australia in 2007 has improved disease control and endoscopic outcomes, but it is unclear if body image has improved in parallel with this. We aimed to determine whether body image and QoL have improved amongst IBD patients with modern IBD car Methods: Tertiary IBD service patients were offered inclusion in the study in 2006 by postal survey (pre-biologic era), and in 2021 by electronic survey (biologic era). Surveys included demographics and history of IBD surgery. In the pre-biologic era (PBE) body image dissatisfaction (BID) and QoL were assessed using a patient reported yes/no question, followed by an open question about how IBD or treatment has changed the way they view their body's appearance. In the biologic era (BE) the validated modified Body Image Scale and Short Inflammatory Bowel Disease Questionnaire were used. Results: The BE included 135 patients, 59% female, mean age 45.9. The PBE included 215 patients, 66% female and mean age 35.5. PBE had 40% reporting IBD surgery vs 36% in BE (P=0.489). BID was observed in 67% vs 39% of the PBE and BE respectively (p<0.01). In the PBE free text responses elicited themes of dissatisfaction with medication or steroid-related appearance changes (41%), bloating (30%), weight gain (28%), weight loss (12%), and specific appearance changes. The link between body image and QoL was mentioned by 33% of patients, with 8% specifically mentioning its impact on their mental health. Females were affected to a greater extent in both PBE (75% vs 52% p<0.01), and BE (50.5% versus 22% p<0.01). In the PBE patients with surgical intervention for IBD had higher rates of BID than those without surgery (81% vs 58%, p<0.01). This association between surgery and BID was not observed in the BE (47% vs 34.9%, p=0.168). In the PBE those with BID were significantly more likely to report impaired QoL(97% vs 71%, p<0.01). This association persisted with time with BE patients with BID also having higher rates of QoL impairment (85% vs 45% p<0.01). Conclusion: Whilst the rate of BID has decreased with modern IBD treatment; it remains highly prevalent and is associated with impaired QoL. Whilst females remain disproportionately affected, the historically observed association between IBD surgery and impaired body image was not demonstrated in the BE. This may reflect improved surgical techniques and biologic down staging prior to surgery. However, body image remains an important Patient Reported Outcome in IBD and warrants further attention.